2023
DOI: 10.3390/ma16020554
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Filler Types on Cellulose-Acetate-Based Composite Used as Coatings for Biodegradable Magnesium Implants for Trauma

Abstract: Magnesium alloys are considered one of the most promising materials for biodegradable trauma implants because they promote bone healing and exhibit adequate mechanical strength during their biodegradation in relation to the bone healing process. Surface modification of biodegradable magnesium alloys is an important research field that is analyzed in many publications as the biodegradation due to the corrosion process and the interface with human tissue is improved. The aim of the current preliminary study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…One study demonstrated that CA-based composite coatings containing hydroxyapatite (HAp) and Mg particles enhanced the corrosion resistance and hydrophilic characteristics of Mg-based implants. [90,91] The most important things to consider in these polymeric coatings are their chemical and biological compatibility with the host tissue and nontoxicity. There are numerous techniques to fabricate high-throughput polymeric coatings, such as Reproduced with permission from.…”
Section: Polymeric Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study demonstrated that CA-based composite coatings containing hydroxyapatite (HAp) and Mg particles enhanced the corrosion resistance and hydrophilic characteristics of Mg-based implants. [90,91] The most important things to consider in these polymeric coatings are their chemical and biological compatibility with the host tissue and nontoxicity. There are numerous techniques to fabricate high-throughput polymeric coatings, such as Reproduced with permission from.…”
Section: Polymeric Coatingsmentioning
confidence: 99%
“…One study demonstrated that CA‐based composite coatings containing hydroxyapatite (HAp) and Mg particles enhanced the corrosion resistance and hydrophilic characteristics of Mg‐based implants. [ 90,91 ]…”
Section: Various Types Of Multifunctional Coatings On Mg Alloysmentioning
confidence: 99%
“…Here are some examples of cellulose-based scaffold materials: Cellulose-acetate-based composite: This composite is used as a coating for biodegradable magnesium implants. The composite includes fillers such as hydroxyapatite and magnesium particles, which have shown positive effects on biocompatibility and surface analysis [ 24 ]. Cellulose-based materials crosslinked with epichlorohydrin: These materials have improved thermal stability, surface area, and swelling degree of hydrogels, making them suitable for implant applications [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose-acetate-based composite: This composite is used as a coating for biodegradable magnesium implants. The composite includes fillers such as hydroxyapatite and magnesium particles, which have shown positive effects on biocompatibility and surface analysis [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This status is conditional on sustainable practices, such as replanting trees to replace those harvested for cellulose production-ensuring CO 2 neutrality as these new plantings mature. Cellulose is available in a wide variety of fibers globally, which contributes to the sustainability and potential environmental friendliness of cellulose-based materials [121,122].…”
mentioning
confidence: 99%